Adipose Tissue Increases the Proliferation of Melanoma Cell Lines In Vitro. Issue 4 (June 2015) - Pallua, Norbert; Paul, Nora E.; Burghardt, Bettina; Fuchs, Paul; Kim, Bong-Sung
<x xml:space="preserve">Abstract</x> Introduction: Autologous fat grafting has been used for reconstructive and aesthetic surgery for more than a century. Although initial criticism involved fat resorption and later the possible radiological interference in mammographies, the most recent debate focuses on the carcinogenicity of fat grafts. Among malignant skin tumors, melanomas show the highest lethality and lead to significant soft tissue defects after resection with fat grafting representing a feasible therapy option for tissue reconstruction. In contrast to breast carcinoma, little data is available regarding the carcinogenicity of fat grafts in melanoma patients. The present study was designed to investigate the influence of whole adipose tissue on the growth of melanoma cell lines compared to breast cancer cell lines. Methods: Human subcutaneous adipose tissue was obtained from elective surgeries and cut into pieces ranging from 20 to 500 mg. Adipose tissue samples were co-cultivated with the human breast cancer cell line MCF-7 and the melanoma cell lines MEL-JUSO and IGR-37, and proliferation was measured using the alamarBlue proliferation assay. Additionally, the same experiment was conducted under nutrient-limited conditions. Results: We found that adipose tissue significantly increased the proliferation of the human breast cancer cell line MCF-7 and importantly also of the melanoma cell lines MEL-JUSO and IGR-37 under optimal nutrient supply. Although the impact of adipose tissue on the growth of MCF-7 cells under nutrient deprivation was comparatively weak, the proliferation of MEL-JUSO and IGR-37 cells was clearly stimulated by adipose tissue. Discussion: Our results show that adipose tissue enhances not only the growth of breast cancer but also melanoma cells even under conditions of nutrient limitation by soluble factors secreted by adipose tissue. With respect to our results and the current literature, reconstruction of soft tissue defects after malignancies including breast cancer and melanoma should be conducted with great care and only after complete tumor resection.